The evolution of dynamic interactions between the knowledge development of powertrain systems. (July 2020) - Mirzadeh Phirouzabadi, Amir; Savage, David; Blackmore, Karen; Juniper, James
Abstract: Competition in the already highly competitive automotive industry intensified in the early 1990's. The ubiquitous internal combustion engine began to be challenged by the upstart alternatives of battery and hybrid electric vehicles, which has led to an intricate web of knowledge development. Our research aims to qualify and quantify the dynamic relationships that formed in the knowledge development of powertrains by adopting conceptual insights from evolutionary ecology. Specifically, the interdependent relationships observed in the Technological Innovation System (TIS) framework is similar to that between species such that powertrain systems can either support or inhibit the knowledge growth of one another over time. Our theoretical framework extends the economics of technical change within technologies vis-à-vis the concept of 'positive and negative externalities' and 'knowledge development co-dynamics'. We use patents data extracted from Thomson Reuters' Derwent Innovations Index to measure the knowledge development in each technological field and apply the biological Lotka-Volterra (L-V) model to analyse the data across three separate time periods 1985–1996, 1997–2007, and 2008–2016. Our results show that the behaviour of the powertrain systems change over time as they have behaved as creative (or uncreative) and explorative (or exploitative). We also demonstrate that the powertrain systems go through temporal transitions where the relationship mode between them changes between amensalism, parasitism, commensalism, and symbiosis. In line with this we recommend that policy makers not only devise strategies (offensive or defensive) for each interaction modes but to also consider changing their strategies when there is transition between the modes. Furthermore, policy makers should consider the dual role of 'creation' and 'destruction' in their innovation policy mixes. Highlights: Powertrain systems interact with one another in terms of knowledge development. They behave as creative (or uncreative) and explorative (or exploitative). Temporal transitions occur in nature, as well as extent and modes of interaction. Positive and negative internalities create positive and negative externalities. Policy makers shall consider both creative and destructive roles of policy mixes.